Factors of emotional burnout in work of rhythmic gymnastics coaches - Kostov, F. F.; Ponomarev, G. N.; Kostyuchenko, V. F. (Theory and Practice of Physical Culture, 2020)
Objective of the study was to profile and analyze the emotional burnout in the national rhythmic gymnastics coaching community.